Toxic Microcystis aeruginosa alters the resource allocation in Daphnia mitsukuri responding to fish predation cues. (1st June 2021) - Lu, Na; Sun, Yunfei; Wei, Junjun; Gu, Lei; Zhang, Lu; Yang, Zhou; Huang, Yuan
Abstract: Many prey organisms adaptively respond to predation risk by inducible defenses with underlying tradeoffs in resource allocation. Cyanobacterial blooms expose zooplankton to poor food conditions, affecting the herbivores' fitness. Given the interferences on resources allocation and life history traits, poor-quality cyanobacteria are predicted to affect the adaptive predator-induced responses in zooplankton. Here, we exposed two clones (i.e., clones SH and ZJ) of the cladoceran Daphnia mitsukuri to different combinations of fish predation cues and diets containing toxic Microcystis aeruginosa (0%–30%). D. mitsukuri matured at a small size and had elongated relative tail spine as adaptive responses to fish cues. Despite the comparable tail spine defense, fish cue-induced changes in growth and reproduction in the clone SH were more pronounced than those in the clone ZJ under no M. aeruginosa . Animals accumulated microcystin in the whole body with increasing abundance of M. aeruginosa . However, the inducible enhanced tail spine allometry was not affected, resulting in unchanged tail spine defense by Daphnia under all M. aeruginosa treatments. By contrast, M. aeruginosa remarkably decreased the adaptive maturation size and the offspring number in all animals. However, the inducible reproductive effort tended to increase or remain unchanged depending on clones associated with the constant or decreased responses of the somatic growth effort under increasing M. aeruginosa . Our results suggested that toxic M. aeruginosa did not alter the resource allocation to antipredator morphological defense but affected the somatic growth and reproduction in D. mitsukuri under fish cues. The present study highlights the different effects of toxic cyanobacteria on adaptive predator-induced responses in zooplankton, promoting the understanding for the morphological defense-mediated predator–prey interactions in eutrophic environments. Graphical abstract: Image 1 Highlights: Anti-predation defenses were predicted to be vulnerable to poor food conditions. Fish-induced resource allocation in Daphnia was studied under toxic Microcystis. Allometric model enabled a mechanistic understanding of the tail-spine defense. Microcystis altered somatic growth and reproduction but not the tail-spine defense. Reponses to cyanobacteria fostered defensive strategy knowledge in zooplankton. Abstract : Toxic M. aeruginosa does not alter resource allocation to morphological defense but affects reproductive and somatic growth performances of D. mitsukuri responding to fish predation cues.